Comparison of salvage chemotherapy regimens and prognostic significance of minimal residual disease in relapsed/refractory acute myeloid leukemia. Issue 1 (2nd January 2021) - Mushtaq, Muhammad Umair; Harrington, Alexandra M.; Chaudhary, Sibgha Gull; Michaelis, Laura C.; Carlson, Karen-Sue B.; Abedin, Sameem; Runass, Lyndsey; Callander, Natalie S.; Fallon, Michael J.; Juckett, Mark; Hall, Aric C.; Hematti, Peiman; et al.
Abstract: We compared the outcomes of salvage chemotherapy in 146 patients with relapsed (57.5%) or refractory (42.5%) AML who received CLAG-M (51%), MEC (39%) or CLAG (10%). Minimal residual disease (MRD) was assessed by flow cytometry. Bivariate, Kaplan–Meier, and Cox regression analyses were conducted. Complete remission (CR) rate of 46% (CLAG-M 54% versus MEC/CLAG 40%, p  = .045) was observed with MRD-negative CR of 33% (CLAG-M 39% versus MEC/CLAG 22%, p  = .042). Median overall survival (OS) was 9.7 months; the longest OS occurred with CLAG-M (13.3, 95%CI 2.4–24.3) versus MEC (6.9, 95%CI 2.9–10.9) or CLAG (6.2, 95%CI 2.4–12.6) ( p  = .025). When adjusted for age, gender, relapsed/refractory AML, poor risk AML, MRD, chemotherapy and transplant, CLAG-M (HR 0.63, 95% CI 0.40–0.98, p  = .042), MRD-negativity (HR 0.15, 95% CI 0.07–0.30, p  < .001) and transplant (HR 0.22, 95% CI 0.13–0.39, p  < .001) were associated with higher OS. Our findings confirm that CLAG-M is a reasonable salvage regimen for RR-AML followed by transplant.